Tic Tac Toe Effectiveness in Teaching English Vocabulary for SD Dana Punia Singaraja Fifth Graders - NI Putu Ayu Niya Loviyani; Ni Nyoman Padmadewi; Luh Gde Rahayu Budiarta (Soshum: Jurnal Sosial dan Humaniora, 2022)
Vocabulary has become an essential element for students to communicate with others. This research intended to analyze students’ vocabulary mastery after being exposed to the Tic Tac Toe game as a learning medium. The total number of the class is 17 students of fifth-grade students of SD Dana Punia Singaraja in the 2021/2022 academic year agreed to participate in this study. This research used pre-experimental research in one group pre-test post-test design. The researcher took the accurate data during six meetings of implementation by teaching them using Tic Tac Toe Game. The Tic Tac Toe game was used as a strategy with the familiar nine grid of the Tic Tac Toe board. It used a vocabulary test with multiple-choice as an instrument. The vocabulary mastery wasimproved from 65.00 to 79.12 in the mean score which means the vocabulary mastery of the students was affected by the implementation of the Tic Tac Toe Game. Besides, Kolmogorov-Smirnov and Levelene Statistic test revealed that the test result was normally distributed and homogeny. Furthermore, the effect size was showing this game has a strong effect on the students’ vocabulary mastery. As a result, the Tic Tac Toe game significantly affected students’ English vocabulary mastery.